Collective Action and Communicative Action in Preservation of Durian Kubang in Sawahlunto City - Yenny Oktavia; Yesi Arza; Lilibeth S Galvez (LPPM Universitas PGRI Sumatera Barat, 2025)
Durian Kubang is a local variety from Sawahlunto City, West Sumatra, which has economic, cultural, and ecological value. However, its existence is threatened by land conversion, aging trees, and low public awareness. This study aims to identify the role of stakeholders, analyze communicative actions, and examine collective efforts in the conservation of Kubang Durian. Referring to the theory of communicative action, conservation is framed as a dialogical and collaborative process that places Durian Kubang as a cultural and ecological heritage. This study uses a qualitative descriptive method with in-depth interview techniques, observation, focus group discussions, and document analysis. The results of the study show that stakeholders such as the Food Security, Agriculture, and Fisheries Service (DKP3), the Instrument Standard Testing Center (BPSI) for Tropical Fruit Crop Agriculture, the [1] Regional Technical Implementation Unit (UPTD), the Seed Supervision and Certification Center (BPSB), and the village government contribute to conservation, but coordination between agencies is still fragmented. Communicative actions occur through meetings, discussions, and digital media, but have not consistently supported long-term collaboration. Collective action is realized through the preservation of mother trees, propagation of superior seeds, farmer training, and promotion of durian-based products. Although it has begun, these efforts are still sporadic and have not been integrated into a comprehensive conservation strategy. The study emphasizes the importance of strengthening coordination and building inclusive communication platforms to support sustainable conservation. By combining five elements of governance capacity—collective action, coordination, resilience, learning, and resources—the research offers a framework for preserving Durian Kubang as a valuable regional heritage